Self-circularizing 5′-ETS RNAs accumulate along with unprocessed pre ribosomal RNAs in growth-stressed Entamoeba histolytica - Gupta, Abhishek Kumar (Nature Publishing Group, 2012)
The primary transcript of rRNA genes is a large pre rRNA which is precisely processed to release the mature rRNAs. The 5′-external transcribed spacer (ETS) of rRNA genes contains important sites for pre rRNA processing. Once the processing is accomplished the ETS is rapidly degraded. We show that in growth-stressed cells of the human parasitic protist Entamoeba histolytica the A'-A(0) sub-fragment of the 5′-ETS accumulates to high levels as a family of RNA molecules of size 666 to 912 nt. These etsRNAs are circular in vivo and can spontaneously self-circularize in vitro. The accumulation of etsRNAs is accompanied by accumulation of unprocessed pre rRNA, indicating a possible role of etsRNAs in inhibition of processing during growth stress. Our data shows for the first time that processed etsRNA is not a mere by-product destined for degradation but is stabilized by circularization and could play a regulatory role as noncoding RNA.